Principles and techniques of biochemistry and molecular biology - Keith Wilson (Cambridge University Press, 2005)
This is a new & expanded edition of the bestselling textbook Principles and Techniques of Practical Biochemistry. This highly popular text has now been fully revised to include techniques from across the biosciences. It focuses particularly on those techniques that have lead to the recent advances in molecular biology and is designed to help students understand the theory and practical principles behind those methods. This book will be essential reading for all bioscience undergraduate students and pre-clinical medical students and will complement traditional undergraduate texts in biochemistry and molecular biology.